Laju Perubahan Moroflogi Sungai Kampar Menggunakan Data Penginderaan Jauh Segmen Rantau Berangin-Bangkinang - Hardi Daim; Mudjiatko Mudjiatko; Sigit Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The increase of population growth has caused damaged to Kampar River becoming and also exploitation for human needs. The exploitation came in the for of riverbed material such as sand and gravel for construction needs. The effect of material mining is the erosions that caused the river to be deeper and also the erosions at the cliff that caused the river to be wider thus causing the disposition of river meander. Remote sensing data is needed to identify the magnitude of erosions and sedimentations on Kampar River so that the change in morphology of Kampar River can be identified. Morphology changes on Kampar River can be identified by means of overlaying the digitized map the previous satellite data with the next satellite data. Thus, the research regarding riverbed material mining of Kampar River to identify the changes of morphology on Kampar River using remote sensing technology.This research used satellite data of Landsat-5 TM, Landsat-7 ETM+ and Landsat-8 OLI TRS which were acquired from United States Geological Survey (USGS). Satellite data which were used are 1994, 2000, 2007, 2010 and 2014 data. The result of the research showed that the erosions on 1994 until 2014 was 1.152.115,56 square meters or 115.211 hectares. Meanwhile the sedimentations on 1994 until 2014 was 1.241.084,95 square meters or 124.108 hectares.Keyword : Morphology, remote sensing, landsat, erosions, sedimentations